Kehidupan Sosial Ekonomi Komunitas Penyuling Minuman Tradisional (Tu Api Tua) Di Desa Hokor Kecamatan Bola Kabupaten Sikka - Yosef Dentis (Ekspektasi: Jurnal Pendidikan Ekonomi, 2017)
The results of the study show that: The socio-economic life of the refiners moke community as a distinctive feature of cultural heritage, the moke drink is also one of the resources that can increase the economic needs of the community, although the results of moke distillation do not fully meet there is also an element of art. Art that comes from how the community how to concoct the moke into a typical preparation, the precesed society in the from of ancestral beverages. The impact of this moke distillation contributes substantially to social change and can elevate people’s live to a better standard of living.